Priorities for Greening and the Sustainable Development of OECD Member Countries and Ukraine: a Comparative Analysis - Olena Dovgal; Nataliia Goncharenko; Olena Reshetnyak; Georgiy Dovgal; Natalia Danko (Comparative Economic Research. Central and Eastern Europe, 2021)
The article focuses on identifying priority areas for greening and sustainable devel-opment for OECD countries and Ukraine. They aim to achieve overall progress inthe interaction between the economy and the environment. Additionally, the aim isto create prerequisites for encouraging innovation and investment tofind new sources of economic growth that are compatible with ecosystems that are capable of recover-ing from damage. It has been demonstrated that although the global goals of greening economies are relevant for all countries, they must be tailored to the regional and national specificities, aswell aseach country's level of economic development. The study used general qualitative and quantitative methods ofeconomic research, including systematic, comparative analysis, methods oflogical and statistical anal-ysis, and index method, among others. The applied theoretical and methodological approach allowed us to identify general trends inthe development of environmental factors inthe OECD countries and Ukraine and their impact on economic growth. Specifically, the study analyzes the current state of affairs and perspectives for green-ing and sustainable development based on a comprehensive assessment of the level of greening in these economies and the relationship between the internal ecological environment - assessed using the indicators of "green growth" - and their economic development. The article also justifies priorities for greening and sustainable devel-opment and suggests practical measures for their implementation. They can serve as a basis for developing apolicy of effective environmental management and elabo-rating anational system of environmentally friendly management and administration.
Keywords: F55; O13; O44; O57; P51; Q56; 330; global environmental problems; global environmental strategy; green growth; greening; priorities for greening and sustainable development